2013
DOI: 10.1017/psrm.2013.16
|View full text |Cite
|
Sign up to set email alerts
|

Economic Voting under Coalition Governments: Evidence from Germany

Abstract: This article analyzes the impact of economic voting in federal elections for the German parliament. It combines theories of coalition politics and cabinet decision making—like prime ministerial government, collective cabinet decision making and ministerial discretion—with theoretical approaches on voting behavior to test which cabinet actor voters reward for improved economic conditions. The empirical results, which are based on data from German national election studies from 1987–2009, show that the party of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 67 publications
(55 reference statements)
3
57
0
2
Order By: Relevance
“…The debit of issue ownership is thus distributed rather unevenly in a coalition government, which lends to the idea that voters have different expectations on coalition partners' ability and responsibility to deliver on economic issues. We can thus contribute to a very recent literature on this matter (e.g., Debus et al 2014;Williams et al 2015) by arguing that if the senior partner is the issue owner, this has rather negative effects on the incumbent, regardless of whether the economic perceptions are negative or positive, while the electoral accountability of the junior partner seems to not be conditional on whether it is considered the issue owner. The results in this study thus offer important insights into retrospective voting mechanisms for parties who serve at different levels of coalition governments.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The debit of issue ownership is thus distributed rather unevenly in a coalition government, which lends to the idea that voters have different expectations on coalition partners' ability and responsibility to deliver on economic issues. We can thus contribute to a very recent literature on this matter (e.g., Debus et al 2014;Williams et al 2015) by arguing that if the senior partner is the issue owner, this has rather negative effects on the incumbent, regardless of whether the economic perceptions are negative or positive, while the electoral accountability of the junior partner seems to not be conditional on whether it is considered the issue owner. The results in this study thus offer important insights into retrospective voting mechanisms for parties who serve at different levels of coalition governments.…”
Section: Discussionmentioning
confidence: 72%
“…Albeit performance voting will not be absent in multiparty coalitions (Duch and Stevenson 2008), the literature has shown that not all incumbent parties are affected equally by retrospective voting (Debus et al 2014;Plescia and Kritzinger 2016;Plescia forthcoming). We will thus not treat the government as a unitary actor, but test our hypotheses at the party level, taking into account the performance evaluations of and ownership attribution to the various coalition parties.…”
Section: Hypothesis 2bmentioning
confidence: 99%
“…For instance, research in political behaviour has repeatedly shown that people's perceptions of the economy act as a filter between the objective economic conditions and electoral choices (e.g. Debus et al 2014). Hence, by looking at respondents' assessments of their own economic self-sufficiency, the CUPESSE data offer a valuable resource to study the individual underpinnings of attitudes that are generally not captured by other indicators of economic performance.…”
Section: Table 1 Description Of the Cupesse Two-generation Survey Datamentioning
confidence: 99%
“…On the other, we can measure the vote share of only the prime minister's (the largest) party in the coalition government. The latter is used for analysis in this paper because voters do not always reward or punish all parties in a coalition government in the same way (Anderson 1995;Debus, Stegmaier, and Tosun 2014). Thus, it is not proper to assume that all parties in a coalition government have the same electoral fortune related to economic success or failure.…”
Section: Methodsmentioning
confidence: 99%